Khmer civilization and Angkor - Snellgrove, David L. (Orchid guides, 2001)
Angkor and the Khmer Civilization presents a concise but complete picture of Khmer cultural history from the Stone Age until the establishment of the French Protectorate in 1863, and is lavishly illustrated with maps, plans, drawings, and photographs. Drawing on the latest archaeological research, Michael D. Coe brings to life Angkor's extraordinary society and culture